212 MART; Is it Able o Create Economical Impacts, Engage Society and Develop Entrepreneurship Culture Within Cociety? - Mulyadi, Didi; Fauzhobihi (International Journal of Science, Technology & Management, 2020)
Abstract. This studies is aimed at analyzing the influence of 212 Mart in developing economic impacts, social engagement and entrepreneurship culture within Moslems society measured by the involvement in the establishment of the 212 Mart. The data were taken from 2 of the 212 Mart located in Bekasi using qualitative and descriptive quantitative in which the interview and questionnaires were conducted simultaneously to gain the needed data. The result found that from the economic impacts, the 212 Mart has not provided the expected results as it needed 4 years return on investment, and the engaging society the Mart has taken into effect the collaboration and cooperation among the members and people in its surrounding while the developing entrepreneurship culture, the 212 Mart has actually brought the energy of togetherness among members as it was built with at least 50 – 100 investors.